Analysis of Translation Methods of Figurative Language in Short Story - Wahyu S. Hadjim; Novriyanto Napu (TRANSBAHASA, 2021)
This research was conducted to find out the translation methods applied by the translator in translating figurative language in O. Henry's short stories. This descriptive analysis research took the data from nine short stories as the research documents. There were 19 pieces of data taken from those nine short stories and analyzed using content analysis. The findings revealed that literal, semantic, communicative, idiomatic, and free translation methods were used in translating simile metaphors and hyperbole. It was found that the literal translation methodwas significantly used compared to other translation methods. The frequent use of literal indicated the poor translation competence of the translators that tended to copy both the structure and meaning of the source text into the target text.